Changes in bone formation regulator biomarkers in early axial spondyloarthritis. (5th September 2020) - Descamps, Elise; Molto, Anna; Borderie, Didier; Lories, Rik; Richard, Corinne Miceli; Pons, Marion; Roux, Christian; Briot, Karine
Abstract: Objective: The hallmark of advanced axial SpA (axSpA) is spine ankylosis due to excessive ectopic bone formation. This prospective study aimed to describe the changes in serum levels of different regulators [sclerostin, dickkopf-1 (DKK-1)] and markers of bone formation [bone morphogenetic protein 7 (BMP-7)] over 5 years in early axSpA patients and to assess determinants of such changes. Methods: The DEvenir des Spondyloarthropathies Indifférenciées Récentes cohort is a prospective, multicentre French study of 708 patients with early (>3 months–<3 years) inflammatory back pain suggestive of axSpA. Serum levels of BMP-7, sclerostin and DKK-1 were assessed at baseline and after 2 and 5 years. Changes in bone formation regulators over time were analysed using mixed linear models. Results: Serum BMP-7 significantly increased over time, with a median relative change of 223.7% [interquartile range (IQR) 0–10 700 (0.17 pg/ml/month), P  < 0.001]. Serum sclerostin significantly increased over time, with a median relative change of 14.8% [IQR −7.9–41.4% (0.001 ng/ml/month), P  < 0.001]. Serum DKK-1 did not significantly change over time. Serum BMP-7 increased over time in active disease (Ankylosing Spondylitis Disease Activity Score with CRP ≥1.3, P  = 0.01), but the increase was less pronounced with TNF inhibitor (TNFi) use ( P  < 0.001). No determinant was associated with serum sclerostin change. Conclusion: Serum BMP-7 change over 5 years was related with inflammation; it was increased in active disease, but the increase was low with TNFi use. Serum sclerostin levels significantly increased over time, but to a lesser degree than for serum BMP-7. Clinical trial registration: https://clinicaltrials.gov/, NCT01648907.